The art of writing a “Title” for an original research paper (Bangladesh Journal of Medical Education, 2023)
This article is a short description on the ‘art of writing a title’ for an original research paper. Readers will get the ‘first impression’ with the title and decide to go further in. In searching journal article and thesis or dissertation, all users use the title as the main source of information. The “title” should not be misleading but be interesting, concise and unique. It is important to include the target terms (the “keywords”) in the title for appropriate indexing and retrieval from the search engines and scientific databases. One must adhere to the style and number of words in the title; suggested for the authors by the target journal or institutional authority. A strong title pulls the reader’s attention and encourage them to read the manuscript. Therefore, drafting a correct title needs careful and meticulous effort.Bangladesh Journal of Medical Education Vol.14(1) January 2023: 70-77